Choosing A Reprocessing Method - Bolding, Barbara (Operating Room Nurses Association of Canada Journal, 2004)
WHICH INSTRUMENT REPROCESSING METHOD IS BEST FOR YOUR PATIENT? The short answer to this question is that there is no single best method. There are many reprocessing methods available to hospitals and to Operating Rooms so any choice will depend on the particular situation at your facility and with your patients. The purpose of this article is to outline the factors to be considered when assessing or comparing reprocessing methods.